Clinical ultrasonography in patients who inject drugs (the CUPID protocol): an illustrated case series - Stephanie C. DeMasi; Laura E. Goyack; Erin F. Shufflebarger; Erik P. Hess; Rachel M. Skains; Maxwell A. Thompson; Samuel Luke Burleson; John P. Gullett; David C. Pigott (Journal of the American College of Emergency Physicians Open)
Abstract In 2017, there were ≈47,600 opioid overdose‐related deaths in the United States. US emergency department (ED) visits for suspected opioid overdose increased by 30% between July 2016 and September 2017.2 The current US opioid epidemic makes it critical for emergency physicians to be aware of common and uncommon infectious and non‐infectious complications of injection drug use. Point‐of‐care ultrasound has become a widely available, non‐invasive diagnostic tool in EDs across the United States and worldwide. The increasing population of injection drug use patients is at risk for serious morbidity and mortality from an array of disease states amenable to ultrasound‐based diagnosis. We propose a protocol for clinical ultrasonography in patients who inject drugs (the CUPID protocol), a focused, 3‐system point‐of‐care ultrasound approach emphasizing cardiovascular, thoracic, and musculoskeletal imaging. The protocol is a screening tool, designed to detect high risk infectious and noninfectious complications of injection drug use.